The protective role of mindfulness and job crafting in mitigating the adverse effects of leader ostracism - Li , Yonghan; Zheng, Pinglian (Transformations In Business & Economics, 2026)
This study seeks to investigate how within the context of the broaden-and-build theory of positive emotions, employees’ positive traits and behaviours can mitigate the negative impacts of leader ostracism on employee innovative behaviour. Data were gathered from 300 employees across various industries through online surveys. Hierarchical regression analyses were conducted to study the associations between the variables. The findings revealed a negative correlation between leader ostracism and employee innovative behaviour. Employee mindfulness was found to be beneficial in reducing the adverse impacts of leader ostracism on employee innovative behaviour. In addition, job crafting, when facilitated by mindfulness, was able to further diminish the negative effect of ostracism on employee innovative behaviour and mediated the moderating role of mindfulness. Mindfulness and job crafting are significant in alleviating the negative impacts of leader ostracism on employee innovative behaviour, offering a new perspective for understanding and improving the phenomenon of leader ostracism in organisations.
Keywords: leader ostracism; employee innovative behaviour; mindfulness; job crafting